Física en la escuela: Un experimento sencillo de magnetismo - Gómez, M. J.; López Álvarez, J. M.; López Sancho, J. M.; Refolio, M. C.; Tiemblo, A. (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2002)
Along this paper we introduce a series of simple experiences illustrating the similarities and the differences among the long-distance interactions that are more familiar to Preschool and Primary Education students, i.e., the magnetic and the gravitational ones. We have tried to find their usefulness both for teachers' training and for their application to education. It was designed in order to show the beauty of the phenomena and the simplicity of the observations. We aim to attract the students' attention and introduce some quantitative aspects by means of the measurement operation.